Development of Flushing Fluids to Prevent Gland Formation on The Chisel - Hallokovich, Umedov Sherali; Nabijonovich, Ashurov Bobirjon (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses how quite often in the practice of drilling plastic pipes on modern dimensional inhibited wash solutions, penetration rate decreases in2-3 times. An analysis of such a drop in mechanical speed indicates as the most influential reasons are the formation of a momentum on the bit and BHA. For the lips injuries of this complication when drilling plastic rocks need to be applied technical and technological solutions. Development of prophylaxis is necessary technical measures that can improve technical and economic indicators drilling plastic rocks. One solution is to use special reagents that prevent gland formation and improve drill ability. Existing directions for solving this problem when drilling inductile rocks are mainly associated with the improvement of the design to lot, improving the quality and organization of the flow of flushing fluid. Improving the design of the bit is carried out by optimization profile weapons bit; hydraulic profile; quantities, sizes, angles of attack and the shape of the cutting elements; location and direction of the prom chisel nozzles. In modern drilling technology for trouble-free plastic sinking rocks often use polymer inhibited flushing fluids. Improving their quality is achieved by introducing additional allowances, the choice of which is based on special scientific research work).